Involvement of oxidative stress in increased peripheral nerve firing during spontaneous dysesthesia in a mouse model of ischemia-reperfusion. (19th September 2016) - Kagaya, Kenta; Sasaki, Atsushi; Kino, Yurika; Taniguchi, Hiroyuki; Kuraishi, Yasushi; Andoh, Tsugunobu
Highlights: Transient ischemia-reperfusion in the hand and foot elicits spontaneous dysesthesia. We established a mouse model of hind-paw transient ischemic-reperfusion. In this model, peripheral nerve activity and lipid peroxidation were increased. An antioxidant reagent countered both the nerve activity and lipid peroxidation. Both oxidative stress and nerve activity may contribute to peripheral dysesthesia. Abstract: Transient ischemia-reperfusion in the hand and foot elicits spontaneous dysesthesia. However, the mechanisms by which this occurs are not completely understood. The objectives of this study were to examine peripheral neural activity related to spontaneous dysesthesia in a mouse model of hind-paw transient ischemic-reperfusion and to investigate the involvement of oxidative stress in this neural activity. The femoral artery and vein were interrupted for 10 min using tourniquet pressure, before the tourniquet was removed to allow reperfusion of the hind paw. Neural activity in the saphenous nerve was recorded during both ischemia and reperfusion. In both the ischemic phase and the reperfusion phase, the frequency of saphenous nerve firing was significantly increased compared to baseline. The antioxidant agent N -acetyl-l -cysteine inhibited significantly the firing of the saphenous nerve in both the maximum and minimum activity periods during ischemia, and in the maximum activity state after reperfusion percentage inhibition being approximately 68%, 60%, and 58%, respectively. In the reperfusion phase, the production of 4-hydroxy-2-noneal, a major product of endogenous lipid peroxidation, was significantly increased in the plantar skin, and this was inhibited by N -acetyl-l -cysteine. In the ischemic phase, a similar trend was observed. These results suggest that an increase in peripheral nerve activity related to oxidative stress may be involved in the spontaneous dysesthesia induced by transient ischemia-reperfusion.